Cooperation between Russia and China in the Creation of Network Universities and Joint Educational Institutions - T. L. Guruleva; N. I. Bedareva (Высшее образование в России)
The article examines such forms of educational cooperation between Russia and China as participation in the activities of the SCO and BRICS Network Universities and the creation of joint educational institutions. The authors have carried out an analysis of educational models of the SCO University and determined the role of the basic Russian and Chinese universities in the implementation of the priority areas of training specialists for the SCO member countries. Educational models, priority training areas planned for implementation at the BRICS Network University, as well as the universities – members of the BRICS branch of the Russian and Chinese sides have been described. The paper dwells on the issue of joint educational institutions in China: the definition of joint institutions used in Chinese regulatory documents has been given, a statistical analysis has been carried out of China’s joint institutions created together with foreign universities. The educational models of four joint educational institutions of Russia and China operating on the territory of the People’s Republic of China are studied. The conclusion was made about the role of Russia and China in the development of the world educational space and the prospects for cooperation between the two countries in creating joint educational institutions.